2005
DOI: 10.1007/s11224-005-8256-x
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses, Crystal Structures, and Magnetic Properties of Carboxylate-Bridged Copper(II) Complexes with Bis(2-Pyridylmethyl)Amino Acids

Abstract: Tetradentate Schiff-base carboxylate-containing ligands, bis(2-pyridylmethyl)amino-5-valeric acid (Hpmva) and bis(2-pyridylmethyl)amino-6-caproic acid (Hpmca), react with copper(II) perchlorate to give rise to the carboxylated bridged chain complexes. These complexes have been characterized by X-ray crystallography, spectroscopic, and variable-temperature magnetic susceptibility measurements. In 1 and 2, each of the copper(II) ions exhibit CuN 3 O 2 coordination environments with the three nitrogen atoms of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…A study on copper(II) complexes is reported in the article by Choi et al [187] in which self-assembling compounds were synthesized with tetradentate Schiff-base carboxylate-containing ligands, bis(2-pyridylmethyl)amino acids. The synthesized compounds were characterized and the X-ray crystal structures determined.…”
Section: Issuementioning
confidence: 99%
“…A study on copper(II) complexes is reported in the article by Choi et al [187] in which self-assembling compounds were synthesized with tetradentate Schiff-base carboxylate-containing ligands, bis(2-pyridylmethyl)amino acids. The synthesized compounds were characterized and the X-ray crystal structures determined.…”
Section: Issuementioning
confidence: 99%